Exploring Motivation and Self-Efficacy in English Language Learning : A Case Study of Fourth-Semester Students at IAIN Takengon - Delfia Herwanis; Qaswafif Muda; Maulida Maulida; Rahmanita Zakaria (Jurnal Pendidikan dan Sastra Inggris, 2025)
This study investigates the role of motivation and self-efficacy in English language learning among fourth-semester students majoring in English at IAIN Takengon. Employing a quantitative method, data were collected from a limited population of five students using a validated Likert-scale questionnaire designed to assess levels of motivation and self-efficacy across key language skills. The results revealed that while students demonstrated high levels of motivation—driven by academic and career goals, as well as personal inspirations—their self-efficacy levels varied, with some showing a lack of confidence in their language abilities. This finding suggests a discrepancy between students’ motivational drive and their self-perceived competence. The study recommends the integration of mentoring programs, engaging classroom strategies, and exposure to authentic language environments to enhance learners’ self-efficacy. These findings contribute to a deeper understanding of affective factors in second language acquisition and provide practical recommendations for language instructors and institutions.